Development A Behavioral Model of Family Planning Participation Among Women Of Reproductive Age Based On Lawrence Green’s Precede–Proceed Framework in Medan City, Indonesia - Nopita Yanti Sitorus; Helfrida Situmorang; Sri Dewi Br Siregar; Desi Handayani Lubis; Yulia Safitri (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Participation of women of reproductive age (WRA) in the family planning (FP) programme in Medan City is only 42.2%, far below the national contraceptive prevalence rate of 59.4%. Existing programmes have not been guided by a locally validated behavioural model. To develop a behavioural model of FP participation among WRA using Lawrence Green’s PRECEDE–PROCEED framework. An analytical cross-sectional study was conducted in 2025 among 260 WRA attending 10 maternity clinics and 3 community health centres (puskesmas) in Medan City, selected by stratified random sampling with proportional allocation. Data were collected with a structured questionnaire measuring predisposing (education, knowledge, attitude, information-seeking behaviour, parity), enabling (income, access to health services, media exposure) and reinforcing (husband’s support, health-worker support) factors. Bivariate analysis used the chi-square test with prevalence ratios (PR) and 95% confidence intervals (CI); variables with p < 0.25 entered a multiple logistic regression (forward stepwise Wald). Forty-two respondents (16.2%) did not participate in the FP programme. Eight of ten variables qualified for multivariable modelling. Four determinants remained significant in the final model: knowledge (AOR = 31.37; 95% CI 12.29–80.06), education (AOR = 17.66; 95% CI 8.03–38.85), husband’s support (AOR = 9.52; 95% CI 4.42–20.50) and income (AOR = 2.83; 95% CI 1.20–6.66). Knowledge was the dominant predictor. A woman with poor knowledge, low education, an unsupportive husband and low income had a predicted probability of non-participation of 99.8%, compared with 0.9% for a woman with none of these characteristics. FP participation in Medan is determined by the interaction of predisposing, enabling and reinforcing factors. Interventions should combine contraceptive literacy education, couple-based counselling and economic empowerment of low-income households Keywords: Contraceptive Behaviour; Family Planning; Logistic Regression; PRECEDE–PROCEED Model; Women of Reproductive Age